1998
DOI: 10.1088/0953-4075/31/24/018
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact ionization of and : contributions from different dissociation channels of multiply ionized molecules

Abstract: The cross sections of ionic products due to the electron impact ionization of N 2 and O 2 have been measured for the electron energies from threshold up to 600 eV. The contributions to the cross sections from the possible reaction channels after the multiple ionization of molecules are also determined. The experiment shows that for both N 2 and O 2 the singly charged fragment N + or O + originates mainly (∼70%) from the contribution of the dissociation of the singly charged parent ions, whereas the doubly char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 38 publications
4
37
0
2
Order By: Relevance
“…Shaw (1992) measured the absolute absorption cross section and the photoionization quantum efficiency from threshold up to 25.6 eV. The N + 2 formation cross section by electron impact has been measured by Tian & Vidal (1998), from threshold up to 600 eV (see the comment of Stebbings & Lindsay (2001) on the accuracy of these cross sections). The N + 2 formation cross section is a maximum (∼1.85 × 10 −16 cm 2 ) for an electron energy of 80-100 eV (Itikawa 2006 (X, v = 1-4) states are also populated, both by autoionization in the case of photoionization and by radiative cascades from excited electronic states.…”
Section: (±25%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Shaw (1992) measured the absolute absorption cross section and the photoionization quantum efficiency from threshold up to 25.6 eV. The N + 2 formation cross section by electron impact has been measured by Tian & Vidal (1998), from threshold up to 600 eV (see the comment of Stebbings & Lindsay (2001) on the accuracy of these cross sections). The N + 2 formation cross section is a maximum (∼1.85 × 10 −16 cm 2 ) for an electron energy of 80-100 eV (Itikawa 2006 (X, v = 1-4) states are also populated, both by autoionization in the case of photoionization and by radiative cascades from excited electronic states.…”
Section: (±25%)mentioning
confidence: 99%
“…Above the double ionization threshold at 42.88 eV, there is a small contribution from N ++ 2 doubly charged ions, which have the same mass-tocharge ratio (m/z) as N + fragment ions. Tian & Vidal (1998) measured the N 2 electron impact ionization cross sections to form N + 2 , N + , and N ++ 2 ions from threshold up to 600 eV electron energy. They found that the N + production cross section reaches a maximum value of 6.6 × 10 −17 cm 2 at 120 eV electron energy (see the review from Itikawa 2006).…”
Section: Productionmentioning
confidence: 99%
“…For the electronic excitation of atomic species, we adopt the cross sections of Stone et al [2002] for H and He, Laher and Gilmore [1990] for O, Goembel [1991, 1992] and Yang and Doering [1996] for N. For electron impact ionization, the cross sections of Bartlett and Stelbovics [2004] are used for H, He and N, and those of Laher and Gilmore [1990] are used for O. For N 2 , the dissociative ionization cross sections are taken from Tian and Vidal [1998b] and Shemansky and Liu [2005], while those for vibrational and electronic excitations from Itikawa [2006]. An additional process of neutral dissociation (N+N) is considered in our calculations, with the cross-section data taken from Cosby [1993].…”
Section: Discussionmentioning
confidence: 99%
“…2-4) are based on data [8,[36][37][38][39][40][41][42]. Total cross-sections of an electron -a nitrogen molecule collision were collected from [43][44][45][46][47] and cross sections of nitrogen molecule ionization from [48][49][50][51]. The excitation of 10 the lowest electronic states (data of [52,53]) and the 8 lowest vibration levels ( [54,55]) of a nitrogen molecule were accounted (Fig.…”
Section: Used Modelsmentioning
confidence: 99%